Accounting Strategies and Corporate Social Responsibility Under Conditions of War - Papinko, Andrii; Mazuryk, Vitalii; Bandurka, Maksym (Journal of Finance and Financial Law, 2025)
The purpose of the article. The purpose of this article is to substantiate the role of strategic accounting in integrating corporate social responsibility (CSR) into business practices under wartime conditions. The study aims to identify how accounting tools can be adapted to reflect the social and ethical responsibilities of enterprises, ensure transparency, and support decision-making processes in an unstable environment. Particular attention is paid to the development of indicators for assessing CSR activities, the challenges of their implementation in accounting systems, and the potential of CSR to enhance business resilience and social trust during military conflict. Methodology. The research combines theoretical and empirical methods. On the theoretical side, the study applies analysis, synthesis, bibliometric review, and historical-logical approaches to conceptualize the relationship between accounting, CSR, and wartime resilience. On the empirical side, 15 semi-structured interviews were conducted with professional accountants and auditors representing both private enterprises and public organizations in Ukraine. Respondents were asked about challenges of financial transparency, ethical dilemmas in CSR reporting, and accounting for wartime social initiatives. Interview data was analyzed through thematic coding, which allowed for the identification of recurring patterns across organizational practices. Results of the research. The research findings demonstrate that under wartime conditions, corporate social responsibility (CSR) has shifted from a reputation-building tool to a critical element of enterprise resilience. Expenditures on shelters, alert systems, employee support, and humanitarian initiatives have become an integral part of management accounting. This requires systematic documentation and analysis of socially oriented costs in order to assess their effectiveness and broader societal impact. The study also revealed that the absence of standardized approaches to recording and evaluating CSR activities complicates transparency and comparability of financial information. Voluntary disclosure of CSR-related data does not ensure consistency, creating risks for the reliability of financial reporting. At the same time, accountants and auditors emphasize the need to develop internal indicators that reflect the social, environmental, and security effects of enterprise activities. Finally, the results indicate that strategic accounting, when combined with CSR, can strengthen trust between business, government, and society. Integrating socially responsible practices into management and reporting systems not only enhances the quality of decision-making but also contributes to the overall resilience of the country during war. This highlights the transformation of CSR from a voluntary initiative into a factor of survival and development for both enterprises and society.